The impact of Yiddish on the English language: an overview of lexical borrowing in the variety of subject areas and spheres of life influenced by Yiddish over time - Landmann, Julia (English today, 2019)
Yiddish has served the English language as a comparatively minor donor language of words and meanings over the course of time. However, Yiddish has provided English with a number of borrowings that have become fairly common in present-day usage. This paper provides a rounded overview of the different lexical domains to which Yiddish contributed in the form of new words and expressions over the centuries, which has been relatively neglected in existing studies. The focus of linguistic concern is on those Yiddish-derived terms that have become established in current English.
Published online by Cambridge University Press: 06 December 2018
Gesehen am 27.08.2019